ANALISIS YURIDIS PEMBATALAN PUTUSAN BAPMI OLEH PUTUSAN PENGADILAN (STUDI PERKARA NOMOR 513/PDT.G-ARB/2012/PN.JKT.PST) - Yohanna Petresia; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Settlement of business disputes be an option for the parties to the dispute are usually used method of dispute resolution through alternative dispute resolution. Choice of dispute resolution in the capital market conducted litigation in general through the arbitration institution Indonesian Capital Market Arbitration Board (BAPMI). BAPMI arbitration decision issued BAPMI-004 / ARB-03 / VIII / 2011 on the application submitted by PT Bank Permata. BAPMI verdict obliging PT Nikko Securities to replace most of the payments made by PT Bank Permata to investors. However, PT Nikko Securities filed a cancellation decision BAPMI the Central Jakarta District Court by reason of deception in BAPMI decision. BAPMI verdict is final, binding and must be implemented immediately canceled by Court decision No. 513 / PDT.G-ARB / 2012 / PN.JKT.PST.This type of research can be classified into types of normative legal research is research that emphasizes the literature data, cover the entire legislation relating to the object of research. Source of data used is primary data, secondary data and data tertiary. Analysis of the data used in this study is qualitative.BAPMI ruling has the force of law, as stated in Article 48 of the Decree of the Indonesian Capital Market Arbitration Board Number: Kep-02 / BAPMI / 11.2009 of the Rules and Events Indonesian Capital Market Arbitration Board. The head of the written decision BAPMI